Effect of CPP-ACP paste with and without CO2 laser irradiation on demineralized enamel microhardness and bracket shear bond strength - Nasrin Farhadian; Loghman Rezaei-Soufi; Seyed Farzad Jamalian; Maryam Farhadian; Shahrzad Tamasoki; Milad Malekshoar; Bahareh Javanshir
ABSTRACT Introduction: Many patients seeking orthodontic treatment already have incipient enamel lesions and should be placed under preventive treatments. The aim of this in vitro study was to evaluate the effect of CPP-ACP paste and CO2 laser irradiation on demineralized enamel microhardness and shear bond strength of orthodontic brackets. Methods: Eighty caries-free human premolars were subjected to a demineralization challenge using Streptococcus mutans. After demineralization, the samples were randomly divided into five equal experimental groups: Group 1 (control), the brackets were bonded without any surface treatment; Group 2, the enamel surfaces were treated with CPP-ACP paste for 4 minutes before bonding; Group 3, the teeth were irradiated with CO2 laser beams at a wavelength of 10.6 µm for 20 seconds. The samples in Groups 4 and 5 were treated with CO2 laser either before or through CPP-ACP application. SEM photomicrographs of a tooth from each group were taken to observe the enamel surface. The brackets were bonded to the buccal enamel using a conventional method. Shear bond strength of brackets and ARI scores were measured. Vickers microhardness was measured on the non-bonded enamel surface. Data were analyzed with ANOVA and Tukey test at the p< 0.05 level. Results: The mean shear bond strength and microhardness of the laser group were higher than those in the control group and this difference was statistically significant (p< 0.05). All groups showed a higher percentage of ARI score 4. Conclusion: CO2 laser at a wavelength of 10.6 µm significantly increased demineralized enamel microhardness and enhanced bonding to demineralized enamel.